Uma intervenção arqueológica nas portas de Braga da Vila de Ponte de Lima - Almeida, Carlos A. Brochado de; Rodrigues, Sandra Raquel da Silva (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This archaeological intervention meant to discover a missing part of the walls from Ponte de Lima and, specifically, one of his emblematic entries: the Portas de Braga. Through it went on ali the traffic that proceeded from the city of Braga, using the ancient roman road Bracara-LimieTude. In the excavated área, limited to a yard, the team os archaeologists could only discover two compartments belonging to a house with a wine press. This building made part of a farmhouse located nearby the city walls. The ceramic materiais found, combined with written documentation, lead to a chronology posterior to the XVI century.